ANALISIS KELAYAKAN BISNIS SYARIAH PADA USAHA MIKRO TEMPE - Heni Sukmawati; Fatimah Zahra Nasution (Universitas Siliwangi, 2019)
Tempe industry is one of potential micro enterprises operating in Indonesia. Tempe isa well-known substitution food consumed by many people in the country. Thus tempeproduction has an important role in meeting the demand for Tempe in the domestic market in Indonesia. Practically in many areas, Tempe production is operated in a small scale due to lack of resources. This promising business is feasible to be developed into a higher scale. The feasibility study is an in-depth assessment in analyzing either a running business or a proposed business plan. The purpose of this study is to define a business condition with a statement that a business is feasible or not as per consideration in various analyzed aspects. In-depth assessment means that one enterprise will be studied comprehensively according to data and information, measured and examined with certain methods. One important aspect is marketing which will look at how large the market share of the business, how capable the business to attain the proportion of the market sharudie, relatively compare with the competitors, what strategies will be conducted in obtaining the expected results for the business. Financial analysis will assess the capability of a business in attaining revenue and minimizing the cost. By doing this analysis, the duration of payback period of an investment will be calculated precisely. The assessment includes financial records and cash flow report. Research method used in this study is descriptive both quantitative and qualitative using survey method and indepth interview. The research designed to capture the real condition regarding the analyzedobject based on valid data and factual circumstances. The collected data then analyzed and processed with the basic theory used in this research. This research was conducted in Tempe production center located on Jalan Ampera Tasikmalaya City. Based on the result from financial analysis, it can be stated that the business is feasible. Based on the result on sharia marketing analysis, it is found that the business is operated accordingly to sharia principles. However, the interview section found some problems regarding the financial management and marketing strategy which needed to be resolutely improved. The research results are expected to be considered as evaluation issue for the improvement and development of Tempe industry in Tasikmalaya City and eventually give some contribution for the economic growth in Tasikmalaya City.